The psychology of sex differences - Jacklin, Carol Nagy; Maccoby, Eleanor Emmons (California: Stanford University Press, 1974)
Contents : Intellect and achievement,perception,learning and memory,intellectual abilities and cognitive styles,achievement motivation and self-concept,social behavior,temperament: activity level and emotionality,social approach-avoidance,one the origins of psychological sex differences,sex typing and the role of modeling.
Includes bibliographical references and index
Keywords: Diferencias Sexuales